2014
DOI: 10.1016/j.ijhydene.2014.05.148
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact and reaction pathway of toluene on a SOFC running on syngas

Abstract: The integration of solid oxide fuel cells (SOFCs) with gasification systems have theoretically been shown to have a great potential to provide highly efficient distributed generation energy systems that can be fuelled by biomass including municipal solid waste. The syngas produced from the gasification of carbonaceous material is rich in hydrogen, carbon monoxide and methane that can fuel SOFCs. However, other constituents such as tar can cause catalyst deactivation, and blockage of the diffusion pathways. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 23 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…Toluene vapour was introduced into H 2 by bubbling. The vapour pressure of toluene P Tol (mm Hg) at a given temperature was calculated using the Antoine equation, which is as following formulas and . Mass concentration of toluene vapour M Tol (g Nm −3 ) was obtained from volume fraction of toluene ν % (formula ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Toluene vapour was introduced into H 2 by bubbling. The vapour pressure of toluene P Tol (mm Hg) at a given temperature was calculated using the Antoine equation, which is as following formulas and . Mass concentration of toluene vapour M Tol (g Nm −3 ) was obtained from volume fraction of toluene ν % (formula ).…”
Section: Methodsmentioning
confidence: 99%
“…Coke production results in the emission of coke oven gas (COG), a mixture of H 2 , CH 4 , and a small amount of unsaturated hydrocarbons. For every 500 million tons of coke that are produced, 210 billion cubic metres of COG are released as a by‐product . Since COG is rich in H 2 and CH 4 , it is a promising fuel with a specific heat in the range of 16 720 to 18 810 kJ m −3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, model tar compounds are used in these studies. Toluene is probably the most used model tar compound . However, also naphthalene and benzene are used.…”
Section: Introductionmentioning
confidence: 99%
“…Doyle et al observed carbon deposition with SEM-EDS analysis, but 20 g/Nm 3 toluene actually increased the cell performance by decreasing the cell ASR and increasing the amount of fuel available due to the tar reforming. Nonetheless, 32 g/Nm 3 dramatically affected the ASR (9). Other studies have used naphthalene (10)(11)(12) and benzene (13,14).…”
Section: Introductionmentioning
confidence: 99%